Faktor-Faktor Yang Mempengaruhi Perilaku Petani Dalam Mengoptimalkan Potensi Sumberdaya Lahan Melalui Usaha Budidaya Ikan Air Tawar (Kolam) Di Kabupaten Tanggamus - Cholid Fatih (Politeknik Negeri Lampung, 2008)
The goal of this research is to know the factors influencing farmers’ behavior in optimizing land resource. This research was conducted at Pagelaran District for fours months from May until August 2007. The research was applied through survey with purposive sampling (60 farmer households). Likert scale was adopted to determine the model with interval answers 1 until 5. The rank of behavior was categorized into three classes: low, middle, and high. The factors influencing farmers’ behavior were determined by path analysis. The result of research has shown that farmers’ behavior were influenced by farmers activity for information search, agricultural extension, and farmers’ knowledge were significant at α 1%. The path analysis shown that the higher to lower factors influencing farmers’ behavior were farmers activities for search information search, agricultural extension, farmers’ knowledge and motivation. Kata kunci: perilaku, motivasi, optimalisasi